Splittringen mellan polska judiska och icke-judiska överlevande från koncentrationsläger. Det svenska samhällets reaktioner våren och sommaren 1945 - Giloh, Mordechay (Nordisk judaistik/Scandinavian Jewish Studies, 2016)
När ungefär 20 000 överlevande från nazisternas koncentrationsläger togs emot i Sverige under våren och sommaren 1945 visste flyktingpersonalen och beslutfattarna bland svenska myndigheter mycket litet om deras bakgrund, kultur och etnicitet. I början dominerade inställningen att antagonismen mellan judar och icke-judar från Polen var en religiös eller etnisk ömsesidig motsättning. Efter ett par månader mognade insikten om splittringen i två separata polska identiteter, samtidigt som antisemitismen hos icke-judiska polacker började nämnas vid sitt rätta namn. En liberalare samhällssyn, flyktingpersonalens personliga erfarenheter samt internationella faktorer samverkade till en bättre förståelse för flyktingarnas situation och för deras behov av att bygga upp ett nytt liv i Sverige där många så småningom rehabiliterades.* * *The division between Polish Jewish and non-Jewish concentration camp survivors: reactions from the Swedish society during the spring and summer of 1945 • As approximately 20,000 survivors from the Nazi concentration camps where received in Sweden during the spring and summer of 1945, the refugee workers and decision makers knew very little about their background, culture and ethnicity. Initially, the general opinion held that the antagonism between Jews and non-Jews from Poland was a mutual religious and cultural conflict and only a few observed the harsh verbal antisemitism that was common among non-Jewish Polish refugees. Over the coming months, an awareness of two separate Polish identities developed and the prevalent antisemitism was recognised for what it was. All persons, who lived within the borders of Poland before the war, were initially classified as Poles but gradually a classification according to religious and ethnic belonging developed. After a few months, the government and authorities realised that it was impossible to demand that all refugees return to their country of origin. A study of the archives of state authorities and aid agencies in Sweden reveals how an increasingly liberal view of society, the personal experiences of the aid workers as well as international circumstances contributed to a deeper understanding of the situation of the refugees and their needs to build a new life in Sweden, where many of them eventually where rehabilitated.